Courting the consumer: consumer preferences and engagement with social-media marketing and horticultural businesses - Reid, Deanna Rose (Kansas State University, 2020)
In recent years, horticultural industry changes, local food movements, fluctuating consumer perceptions and motivations to buy fresh produce and plants, and new online marketing opportunities have impacted small and rural horticultural businesses. As horticultural product shopping habits have changed and advances in social media technology have been made, horticultural businesses need to update marketing practices. The purpose of this study was achieved through research objectives and a research question which defined relevant and effective social-media post components in regard to consumer likelihood of online social-media engagement, willingness to travel, and willingness to purchase horticultural goods. . Previous research confirmed social media, specifically Facebook, allows horticultural businesses to connect with potential clients; however, research shows that business owners are uncertain about how to transition from using traditional-media marketing to social-media marketing. Additionally, business owners have different opinions than their consumers about the most effective use of Facebook marketing. Being aware of preferences and audience’s desires allows horticultural businesses to create effective social-media marketing content that will increase sales and profit. This empirical research was conducted to determine the effects of Facebook posts and images on horticultural consumer engagement and purchasing behaviors While attracting attention to a featured product and making advertising campaigns attractive to consumers is relevant, this study sought to operationalize consumer central processing through the framework of social-media engagement; therefore, the ELM was the most relevant to use for identifying consumer Facebook content preferences for horticultural businesses. The ELM, introduced in 1981 by Petty and Cacioppo, states that messages with information relevant and thought-provoking to the recipient are far more likely to stimulate central processing than advertisements with which people cannot connect. Social-media post components that are appealing to consumers receive the most amount of interaction and central processing. Emotion toward advertisements and images guides cognitive processing, so appealing to consumers’ needs and desires is important. In order to determine what type of social-media content was most effective and engaging, orthogonal conjoint design was used. Three online surveys featuring common horticultural products, garden petunias (Petunia hybrid), bell peppers (Capsicum annuum), and apples (Malus pumila), were used to represent bedding plant, direct-marketed produce, and pick-your-own produce businesses in the horticultural industry and were disseminated to Midwestern U.S. residents. Survey questions asked about consumer preferences for and likelihood of engagement with horticultural business posts on social media and the likelihood of purchasing horticultural products after viewing Facebook posts. Results of this study show features of Facebook posts do impact consumer engagement. Consumers are more likely to “like” posts, as the “like” emoji is the default reaction on Facebook, thus, interaction requires little effort. Promotional messages (672, 54.1%) were found to be the most engaging in horticultural Facebook posts. This study found bedding plant posts featuring petunias were preferred by consumers over direct-marketed and pick-your-own produce posts containing images of and information about bell peppers and apples, respectively. Flowers garnered the most positive reactions; whereas, apples and peppers received a mixture of mostly positive and some negative emoji reactions, indicating flowers are more popular than produce among Midwestern consumers. Produce and food items are considered necessity goods; therefore, it is possible consumers were generally less interested in the produce featured in this study. Distance of a business’s location from social-media users’ residence also influenced engagement, and most consumers were willing to “like” posts from businesses located one hour away or in the region. Respondents were less willing to share or comment on posts, in general, but were especially unlikely to do so for businesses outside of their region or located elsewhere in their state of residence. When asked about likelihood of purchasing horticultural products after viewing Facebook posts, all survey respondents indicated, in general, a higher likelihood of purchasing in-store from horticultural businesses after viewing posts featuring people with products (n = 754, 63.5%) and educational messages (n = 654, 52.7%). Bedding plant consumers were more willing to purchase horticultural products after seeing them featured on Facebook than direct-marketed and pick-your-own produce shoppers. Results of this study show promotional and educational messages and images featuring products at a business or people with products are the most engaging and evoke emotion, thus, should be incorporated in independent horticultural business social-media campaigns.
Keywords: Horticultural marketing; Horticulture; Social media; Facebook; Social-media marketing; Elaboration likelihood model